SHELF LIFE AND SENSORY QUALITY OF VALUE ADDED CARABEEF NUGGETS UNDER FREEZER STORAGE - K. Dushyanthan; R. Narendra Babu; Vasanthi Suresh; R. Ramani; Robinson.J.J.Abraham (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted with the objective of assessing the microbiological and organoleptic properties of low value meat (25%) incorporated buffalo meat nuggets during frozen storage (-18°C) for a period of 180 days. Binders like Refined Wheat Flour (7%,), Soy Flour (3%), Whole Egg (1%) and Liquid Whey (3%) were incorporated in treatment samples, while control was prepared with skeletal meat alone incorporating Refined Wheat Flour @ 5%. Results of the study revealed that the control nuggets had the lowest anaerobic (3.37±0.05) count (AC) and highest sensory scores for appearance (6.93±0.04) and flavour (6.74±0.05). Juiciness scores (6.44±0.05) and overall acceptability (7.18±0.54) was rated highest in RWF incorporated nuggets; while the LW incorporated nuggets had the highest tenderness scores (6.65±0.10) with lowest Total viable (3.81±0.06) count (TVC) and Yeast and Mould (4.07±0.01) count (YMC). Microbial and the organoleptic scores decreased on storage, however, vacuum packed nuggets had better scores of sensory and shelf life. It is concluded that in addition to value addition in terms of vacuum packaging, utilisation of by product of paneer (liquid whey) and utilisation of low value meat in nuggets had shelf stability in terms of microbial quality as well highest acceptability up to 180 days of frozen condition.